Two-electron reductive carbonylation of terminal uranium(V) and uranium(VI) nitrides to cyanate by carbon monoxide - Cleaves, Peter A.; King, David M.; Kefalidis, Christos E.; Maron, Laurent; Tuna, Floriana; McInnes, Eric J.L.; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; Liddle, Stephen T. (Wiley-VCH Verlag, 2014)
Two-electron reductive carbonylation of the uranium(VI) nitride [U(TrenTIPS)(N)] (2, TrenTIPS=N(CH2CH2NSiiPr3)3) with CO gave the uranium(IV) cyanate [U(TrenTIPS)(NCO)] (3). KC8 reduction of 3 resulted in cyanate dissociation to give [U(TrenTIPS)] (4) and KNCO, or cyanate retention in [U(TrenTIPS)(NCO)][K(B15C5)2] (5, B15C5=benzo-15-crown-5 ether) with B15C5. Complexes 5 and 4 and KNCO were also prepared from CO and the uranium(V) nitride [{U(TrenTIPS)(N)K}2] (6), with or without B15C5, respectively. Complex 5 can be prepared directly from CO and [U(TrenTIPS)(N)][K(B15C5)2] (7). Notably, 7 reacts with CO much faster than 2. This unprecedented f-block reactivity was modeled theoretically, revealing nucleophilic attack of the π* orbital of CO by the nitride with activation energy barriers of 24.7 and 11.3 kcal mol−1 for uranium(VI) and uranium(V), respectively. A remarkably simple two-step, two-electron cycle for the conversion of azide to nitride to cyanate using 4, NaN3 and CO is presented.